Perancangan Aplikasi Usaha Kecil Mikro dan Menengah Berbasis Mobile Android (Studi Kasus : Sentra UMKM Tingkir Lor-Salatiga) - Kresna Prasmadewa; Radius - Tanone (Jurnal Teknik Informatika dan Sistem Informasi, 2016)
Abstract â€” Empowerment SME (Small and Medium Enterprise) was a step for Dinas Perindustrian Perdagangan dan Koperasi (Disperindagkop) Salatiga to answer one vision to create empowerment public economics to increase productivity to head a independent and prosperous public in Salatiga. According to data Dinas Perindustrian Perdagangan dan Koperasi (Disperindagkop) Salatiga, in 2016 there are 2730 units SME (Small and Medium Enterprise) registered. There are one of many problems in SMEs there was no media to promote SMEs for public to know and find out the SMEs product in Salatiga. This situation basically happen whole in most region in Indonesia. This research is to design and implement android based applications for promote SMEs in Salatiga. This application is usefull for promote SMEs product in Salatiga with support of LBS (Location Based Service) and Google Cloud Messaging (GCM).Â